T. gondii rhoptry protein ROP18 induces apoptosis of neural cells via endoplasmic reticulum stress pathway - Lijuan Wan; Lingli Gong; Wei Wang; Ran An; Meijuan Zheng; Zongru Jiang; Yuewen Tang; Yihua Zhang; He Chen; Li Yu; Jilong Shen; Jian Du (Parasites & Vectors, 2015)
Abstract Background The neurotropic parasite T. gondii is widespread among mammalian hosts including humans. During the course of T. gondii infection, the central nervous system is the most commonly damaged of all invasive organs. The polymorphic rhoptry protein ROP18 has been identified as a key factor in the pathogenesis of T. gondii; however, the molecular mechanism by which this protein exerts neuropathogenesis remains elusive. Methods Immunofluorescence staining was performed to detect neuropathogenesis of the mouse brain tissues. The apoptosis of neural cells and the expressions of related proteins in the endoplasmic reticulum stress (ER Stress)-mediated apoptosis pathway were detected by flow cytometry and Western blotting. Results Immunofluorescence staining reveals induction of the propidium iodide (PI) - positive neural cells in mouse cerebral cortex and hippocampus infected with ROP18 over-expressing transgenic tachyzoites. Western blotting analyses reveal that ROP18 increases the expressions of cleaved caspase-12, CHOP and cleaved caspase-3 when compared to the control groups. After the pretreatment of Z-ATAD-FMK (a specific caspase-12 inhibitor), the apoptotic level of neural cells had an apparent decline, and correspondingly, the expressions of those related proteins were notably decreased. Conclusions Our findings here highlight that the virulence factor ROP18 in T. gondii may contribute to neuronal apoptosis through the ER stress-mediated apoptosis pathway, which may be a potential molecular mechanism responsible for neurological disorders of toxoplasmosis.